Multicultural Interactions in International Trading: State- Owned Company Employees’ Perspectives - Nadya, Nanda; Silvhiany, Sary; Inderawati, Rita (Indonesian Research Journal in Education |IRJE|, 2024)
In the context of international business activity in open market trade areas, multicultural interaction among customers overseas and state-owned company employees has become increasingly common place. The ASEAN Free Trade Area, established in 2015, has encouraged an open market wherein meetings and transactions among people with different backgrounds occur. This paper focuses on the engagement between customers from diverse backgrounds and employees of state-owned companies. Employing a qualitative approach anchored in a case study, we examined multicultural interactions, presenting a vibrant marketplace where individuals from various nations converge to exchange goods and services. This study draws upon data from observations of the interactions and in-depth interviews with seven employees working in the docking area.  The data were analyzed using thematic analysis. The findings of this study highlight cultural sensitivity in communication and global translingual communication strategies. In detail, the paper reveals employees' diverse experiences as they navigate interactions with overseas customers in the field of international trade. These findings summarize various insights, highlighting cross-cultural encounters' challenges, opportunities and dynamics. By explaining interactions and employees’ vantage point of their experience, this research contributes to a deeper understanding of the interactions between diverse interests in global markets, thereby offering valuable implications for those involved.